PEMILIHAN SOLUSI PENERAPAN BRING YOUR OWN DEVICE (BYOD) BERDASARKAN KONTROL KEAMANANNYA - Moh. Idris (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : The term BYOD (Bring Your Own Device) refers to the use of employees' personal devices (for example smartphones, tablets, laptops, netbooks) to do their work and manage corporate data from anywhere at any time. BYOD has been widely applied in the business world, hospitals, and education. With the ease that can be achieved by using BYOD, the security aspect is very important to consider. It starts with the security of the device to the security of company data that can be accessed by employees. Five dimensions of security control that must be considered in implementing BYOD: 1) data control; 2) access control; 3) network access control; 4) device management; 5) create a supporting framework. With the five BYOD implementation solutions presented in this study, there is only one solution that accommodates the five dimensions of BYOD security control, the use of Mobile Device Management (MDM) technology.